Penerapan Pemasaran Digital dalam Meningkatkan Akses Pasar UMKM (Studi Kasus pada UMKM Rosyana Collection di Kabupaten Pekalongan) - Gunawan Aji; Putri Wulan Sari; M. Riyyan (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2023)
The presence of digital technology is used as a sign of technological change in a more advanced direction, one of which is the existence of the internet. The existence of the internet provides an opportunity for MSMEs to promote their products easily and efficiently. This promotion can be carried out using digital marketing which can increase market access. The aim of this research is to find out the marketing strategies implemented by Rosyana Collection MSMEs and the obstacles they face in marketing. The research method used is descriptive with a qualitative approach sourced from interviews and direct quotations from written sources. The results obtained from this research are that digital marketing provides benefits for MSMEs because they are able to promote their products easily and get high profits. This has caused Rosyana Collection MSME players to implement several digital marketing strategies so that their products can be sold optimally. These strategies include utilizing social media, promoting with content, and others. However, apart from the benefits obtained, there are also obstacles faced such as bad signals, late deliveries, and fraud. So, it can be concluded that the application of digital marketing provides benefits for MSMEs in marketing their products, but there are also obstacles they face.